Preparation method of PE embossed breakpoint release film
By modifying polydimethylsiloxane and cerium-containing compounds, the prepared PE embossed breakpoint release film solves the problem of silicone oil residue in the silicone release film, improves the release force stability and weather resistance at high temperatures, and is suitable for high-end applications.
Patent Information
- Application Number
- CN202510967021.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-08-26
AI Technical Summary
The existing silicone release film has silicone oil residue problems during the recycling process, resulting in a decline in the performance of recycled materials and serious transfer of silicone oil at high temperatures, affecting the viscosity of the paste. Moreover, the non-silicon release film has disadvantages in release force range, weather resistance and cost, making it difficult to be applied to high-end scenarios.
Using the modification method of modified polydimethylsiloxane and cerium-containing polymetallic organic compounds, a PE embossed breakpoint release film is prepared through free radical copolymerization and the use of crosslinking agents to improve its thermal stability and weather resistance at high temperatures and avoid silicone oil residues.
The prepared PE embossed breakpoint release film maintains good release force stability at high temperatures, reduces silicone oil residues, and is suitable for high-end electronics, new energy and automobiles.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of film materials, and in particular relates to a method for preparing a PE embossed breakpoint release film. Background Art
[0002] In the release film sector, silicone release films, with their unique low surface energy properties, dominate the market in terms of release force regulation (1-1000g / inch) and processing adaptability. Their addition-type systems, cured via platinum catalysis, rapidly form a stable release layer at high temperatures, making them suitable for a variety of substrates, including PE, PET, and PP. However, the problem of residual silicone oil in silicone release films has long restricted their application: during the recycling process, residual silicone oil is difficult to decompose, resulting in a decline in the performance of the recycled material and the introduction of organic pollutants. Furthermore, at high temperatures, silicone release films experience significant silicone oil transfer (residual adhesion rate ≤ 90%), significantly reducing the adhesion of the adhered substrate. This is particularly true in the protective film sector, where silicone oil transfer can lead to adhesive failure.
[0003] To address these issues, existing technologies often utilize non-silicone release films. For example, Chinese Patent CN105348946B discloses a matte release film based on a non-silicone acrylic resin. While this film avoids silicone oil residue, it has a narrow release force adjustment range and poor stability, potentially leading to release force loss and failure at high temperatures. Another example is the ultra-light fluorine release film disclosed in Chinese Patent CN116120614B. While it exhibits excellent temperature resistance (230-240°C) and chemical stability, its release force remains relatively high, and its cost and environmental friendliness are questionable, limiting its widespread adoption. While non-silicone release films offer advantages in silicone transfer, their combined disadvantages in release force range, weatherability, mechanical properties, and cost make them currently only suitable for mid- to low-end applications (such as general packaging and label paper). Silicone release films will continue to be irreplaceable in high-end electronics, new energy, automotive, and other fields. Therefore, developing a silicone release film with low silicone oil residue, excellent weather resistance and controllable cost has become a technical problem that the industry urgently needs to solve. Summary of the Invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these objects and other advantages of the present invention, a method for preparing a PE embossed breakpoint release film is provided, comprising the following steps: Step 1: dissolving modified polydimethylsiloxane and a cross-linking agent in a solvent, adding a catalyst and a regulator, stirring evenly, and filtering to obtain a release agent; Step 2: Use a flattening roller to eliminate wrinkles on the PE film, then perform corona treatment on the PE film, apply a release agent on the PE film and heat-cure it to obtain a release film; Step 3: Use an embossing machine to emboss the release film into patterns, then mark breakpoints, and finally roll it up to obtain a PE embossed breakpoint release film.
[0006] Preferably, in step 1, the mass ratio of modified polydimethylsiloxane, cross-linking agent, solvent, catalyst and regulator is 10-15:4-6:60-70:0.3-0.5:5-10.
[0007] Preferably, in step 1, the crosslinking agent is one of hydrogen-containing silicone oil or methyl hydrogen-containing silicone oil, the solvent is one of toluene, xylene, dichloromethane, chloroform, tetrahydrofuran, and ethyl acetate; the catalyst is a platinum catalyst; and the regulator is one of stearic acid, butyl stearate, oleamide, ethylene bisstearamide, polyethylene wax, or silicone resin.
[0008] Preferably, in step 1, the stirring speed is 300-500 rpm, and the stirring is carried out at 30-40° C. for 1-2 h.
[0009] Preferably, in the step 2, corona treatment is performed in a corona device for 20 to 30 minutes at a corona voltage of 50 to 60 kV.
[0010] Preferably, in the step 2, the release agent is coated with a thickness of 0.05-0.08 mm, the curing temperature is 60-80° C., and the heating time is 8-10 min.
[0011] Preferably, the preparation method of the modified polydimethylsiloxane in step 1 is specifically as follows: S1. Dissolve polydimethylsiloxane in isooctane, then add hydroxyethyl acrylate, then add azobisisoheptanenitrile and N,N-methylenebisacrylamide, and heat to react for a period of time under an argon atmosphere; S2, adding the cerium-containing organic compound to the system after the reaction in S1, heating and reacting for a period of time under an argon atmosphere again, and then cooling to room temperature, turning off the argon, filtering the solid-liquid mixture under reduced pressure, and collecting the filtrate; S3. The filtrate is transferred to a degassing reactor, and low-boiling substances are removed under argon protection. After completion, the temperature is cooled to room temperature, and the argon is turned off to obtain modified polydimethylsiloxane.
[0012] Preferably, in S1, the mass ratio of polydimethylsiloxane, isooctane, hydroxyethyl acrylate, azobisisoheptonitrile and N,N-methylenebisacrylamide is 1:8-10:0.4-0.5:0.02-0.03:0.02-0.03, and the heating reaction is carried out at a temperature of 80-90° C. for 6-8 hours.
[0013] Preferably, in S2, the amount of the cerium-containing organic compound added is 3-5 wt% of the initial polydimethylsiloxane, the cerium-containing organic compound is one or more of cerium acetylacetonate, cerium acetylacetonate hydrate, and cerium isooctanoate, the heating temperature is 180-200° C., and the heating time is 12-18 hours.
[0014] Preferably, in said S3, the operation temperature for removing low boiling materials is 220-250°C, the operation time is 3-6 hours, and the absolute pressure is 10 -5 ~3000Pa.
[0015] The present invention includes at least the following beneficial effects: by adding hydroxyethyl acrylate to polydimethylsiloxane for a free radical copolymerization reaction, the stability of the obtained release agent is improved; and the polydimethylsiloxane is further modified with a cerium-containing multi-metal organic compound to make the release agent have good thermal stability and heat resistance in air and high temperature, and can effectively prevent silicone from remaining on the surface of the adhesive material. DETAILED DESCRIPTION The present invention is further described in detail below with reference to the embodiments so that those skilled in the art can implement the invention with reference to the description.
[0016] Example 1 A method for preparing a PE embossed breakpoint release film comprises the following steps: Step 1: First prepare modified polydimethylsiloxane, specifically comprising: S1. Dissolve 2 kg of polydimethylsiloxane in 20 kg of isooctane, then add 0.8 kg of hydroxyethyl acrylate, 0.04 kg of azobisisoheptanenitrile and 0.04 kg of N,N-methylenebisacrylamide, and heat to 85 ° C under argon atmosphere for 8 hours; S2, adding 0.06 kg of cerium isooctanoate to the system after the reaction in S1, heating to 180 ° C under argon atmosphere again for 18 hours, then cooling to room temperature, turning off the argon, filtering the solid-liquid mixture under reduced pressure, and collecting the filtrate; S3, the filtrate was transferred to a de-low boiling reaction kettle, and the low boiling point removal operation was performed under argon protection. The low boiling point removal operation temperature was 220°C, the operation time was 3 hours, and the absolute pressure was 200 Pa. After the low boiling point removal operation was completed, the temperature was cooled to room temperature, the argon was turned off, and the product was taken out to obtain a modified polydimethylsiloxane with a viscosity of 5000~8000cps; Then, 1 kg of modified polydimethylsiloxane and 0.4 kg of hydrogenated silicone oil were dissolved in 6 kg of toluene, and 0.03 kg of platinum catalyst and 0.5 kg of butyl stearate were added, stirred evenly, and filtered to obtain a release agent; Step 2: Use a flattening roller to eliminate wrinkles on the PE film, then place the PE film in a corona device for corona treatment at a corona voltage of 50KV for 25 minutes to obtain a corona-treated PE film, apply a release agent on the PE film to a thickness of 0.05mm, and then heat-cure at 60°C for 10 minutes to obtain a release film; Step 3: Use an embossing machine to emboss the release film into patterns, then mark breakpoints, and finally roll it up to obtain a PE embossed breakpoint release film.
[0017] Example 2 A method for preparing a PE embossed breakpoint release film comprises the following steps: Step 1: First prepare modified polydimethylsiloxane, specifically comprising: S1. Dissolve 2 kg of polydimethylsiloxane in 20 kg of isooctane, then add 0.8 kg of hydroxyethyl acrylate, 0.04 kg of azobisisoheptanenitrile and 0.04 kg of N,N-methylenebisacrylamide, and heat to 85 ° C under argon atmosphere for 8 hours; S2, adding 0.06 kg of cerium isooctanoate to the system after the reaction in S1, heating to 180 ° C under argon atmosphere again for 18 hours, then cooling to room temperature, turning off the argon, filtering the solid-liquid mixture under reduced pressure, and collecting the filtrate; S3, the filtrate was transferred to a de-low boiling reaction kettle, and the low boiling point removal operation was performed under argon protection. The low boiling point removal operation temperature was 220 ° C, the operation time was 3 hours, and the absolute pressure was 200 Pa. After the low boiling point removal operation was completed, the temperature was cooled to room temperature and the argon was turned off to obtain modified polydimethylsiloxane; Then, 1.2 kg of modified polydimethylsiloxane and 0.5 kg of hydrogenated silicone oil were dissolved in 7 kg of xylene, and 0.05 kg of platinum catalyst and 0.8 kg of oleamide were added, stirred evenly, and filtered to obtain a release agent; Step 2: Use a flattening roller to eliminate wrinkles on the PE film, then place the PE film in a corona device for corona treatment at a corona voltage of 50KV for 25 minutes to obtain a corona-treated PE film, apply a release agent on the PE film to a thickness of 0.05mm, and then heat-cure at 60°C for 10 minutes to obtain a release film; Step 3: Use an embossing machine to emboss the release film into patterns, then mark breakpoints, and finally roll it up to obtain a PE embossed breakpoint release film.
[0018] Example 3 A method for preparing a PE embossed breakpoint release film comprises the following steps: Step 1: First prepare modified polydimethylsiloxane, specifically comprising: S1. Dissolve 2 kg of polydimethylsiloxane in 20 kg of isooctane, then add 0.8 kg of hydroxyethyl acrylate, 0.04 kg of azobisisoheptanenitrile and 0.04 kg of N,N-methylenebisacrylamide, and heat to 85 ° C under argon atmosphere for 8 hours; S2, adding 0.06 kg of cerium isooctanoate to the system after the reaction in S1, heating to 180 ° C under argon atmosphere again for 18 hours, then cooling to room temperature, turning off the argon, filtering the solid-liquid mixture under reduced pressure, and collecting the filtrate; S3, the filtrate was transferred to a de-low boiling reaction kettle, and the low boiling point removal operation was performed under argon protection. The low boiling point removal operation temperature was 220 ° C, the operation time was 3 hours, and the absolute pressure was 200 Pa. After the low boiling point removal operation was completed, the temperature was cooled to room temperature and the argon was turned off to obtain modified polydimethylsiloxane; 1.5 kg of modified polydimethylsiloxane and 0.6 kg of methyl hydrogen silicone oil were dissolved in 7 kg of dichloromethane, and then 0.05 kg of platinum catalyst and 1 kg of polyethylene wax were added. The mixture was stirred and filtered to obtain a release agent. Step 2: Use a flattening roller to eliminate wrinkles on the PE film, then place the PE film in a corona device for corona treatment at a corona voltage of 50KV for 25 minutes to obtain a corona-treated PE film, apply a release agent on the PE film to a thickness of 0.05mm, and then heat-cure at 60°C for 10 minutes to obtain a release film; Step 3: Use an embossing machine to emboss the release film into patterns, then mark breakpoints, and finally roll it up to obtain a PE embossed breakpoint release film.
[0019] Example 4 A method for preparing a PE embossed breakpoint release film comprises the following steps: Step 1: dissolve 2 kg of polydimethylsiloxane in 20 kg of isooctane, then add 0.8 kg of hydroxyethyl acrylate, then add 0.04 kg of azobisisoheptane and 0.04 kg of N,N-methylenebisacrylamide, heat to 85 ° C under an argon atmosphere for 8 hours, then raise the temperature to 120 ° C and continue heating for 12 hours to remove isooctane to obtain only copolymer-modified polydimethylsiloxane; then dissolve 1 kg of only copolymer-modified polydimethylsiloxane and 0.4 kg of hydrogen-containing silicone oil in 6 kg of toluene, add 0.03 kg of platinum catalyst and 0.5 kg of butyl stearate, stir evenly and filter to obtain a release agent; Step 2: Use a flattening roller to eliminate wrinkles on the PE film, then place the PE film in a corona device for corona treatment at a corona voltage of 50KV for 25 minutes to obtain a corona-treated PE film, apply a release agent on the PE film to a thickness of 0.05mm, and then heat-cure at 60°C for 10 minutes to obtain a release film; Step 3: Use an embossing machine to emboss the release film into patterns, then mark breakpoints, and finally roll it up to obtain a PE embossed breakpoint release film.
[0020] Comparative Example 1 A method for preparing a PE embossed breakpoint release film comprises the following steps: Step 1: Dissolve 1 kg of polydimethylsiloxane and 0.8 kg of hydrogenated silicone oil in 6 kg of toluene, then add 0.03 kg of platinum catalyst and 0.5 kg of butyl stearate, stir well, and filter to obtain a release agent; Step 2: Use a flattening roller to eliminate wrinkles on the PE film, then place the PE film in a corona device for corona treatment at a corona voltage of 50KV for 25 minutes to obtain a corona-treated PE film, apply a release agent on the PE film to a thickness of 0.05mm, and then heat-cure at 60°C for 10 minutes to obtain a release film; Step 3: Use an embossing machine to emboss the release film into patterns, then mark breakpoints, and finally roll it up to obtain a PE embossed breakpoint release film.
[0021] Comparative Example 2 A conventional silicone release film was used, and the preparation method referred to patent CN110819261B: 100 kg of vinyl-terminated polydimethylsiloxane, 2.8 kg of methyl hydrogenated silicone oil, 0.7 kg of amino silicone oil, and 0.3 kg of methyl fluorosilicone oil were added to a container, the stirring speed was controlled to 300-500 rpm, and the mixture was stirred in a closed state for 5 minutes; then 0.5 kg of spherical silica powder and 0.3 kg of white carbon black were added, and the mixture was stirred at 1800 rpm for 2 hours, followed by the addition of 1 kg of anchoring agent, 0.1 kg of inhibitor, and 300 kg of toluene, the stirring speed was controlled to 300-500 rpm, and the mixture was stirred in a closed state for 5 minutes; finally, 3 kg of platinum catalyst was added, and the silicone release agent was obtained after closed stirring for 5 minutes, which was then coated on a PE film to obtain a silicone release film.
[0022] The products obtained from Examples 1-4 and Comparative Examples 1-2 were subjected to the following performance tests according to industry standards: 20 min release force, aging release force, high temperature release force, and residual rate.
[0023] The 20-minute release force test method is as follows: First, apply tesa™ 7475 adhesive tape to the release surface of the release film to be tested. After rolling back and forth three times with a 2kg roller, cut the tape into a 25mm x 130mm strip. After the strip is left at room temperature for 20 minutes, apply it to a steel plate with adhesive. The tape is peeled off at an angle of 180° and a peel speed of 300mm / min using a tensile testing machine. The reading on the tensile testing machine is the 20-minute release force.
[0024] The aging release force test method is as follows: the test conditions are the same as the 20-min release force test conditions, except that the specimen is placed at room temperature for 24 hours and is pressed under a glass plate. The result measured after the specimen is taken out at the end of the time is the aging release force.
[0025] The high-temperature release force test method is as follows: the test conditions are the same as the 20-minute release force test conditions, except that the specimen is placed at 200°C for 20 minutes and is pressed tightly under a glass plate. The result measured after the specimen is taken out at the end of the test period is the high-temperature release force.
[0026] The residual rate test method is as follows: Apply standard NITTO™ 31B tape to the release surface to be tested and roll it back and forth three times with a 2kg roller. Cut a 25mm x 300mm specimen and place it horizontally between two glass plates. The glass plates are placed at 70°C, 50% RH, and under the pressure of a 2kg weight for 20 hours. After cooling at room temperature for 4 hours, remove the specimen and slowly peel the 31B standard tape from the release film. The specimen is then applied to a steel plate and rolled back and forth with a 2kg electric roller at a speed of 300mm / min under its own weight. Roll the tape back and forth twice at a speed of 300 mm / min, leave it for 20 minutes, and peel off the tape on a tensile testing machine at a speed of 300 mm / min. The average peeling force read on the tensile testing machine is recorded as L1. A new 31B standard tape (the same roll as the tape used for sticking the specimen) is directly attached to the steel plate and rolled back and forth twice at a speed of 300 mm / min under its own weight. Leave it for 20 minutes and peel off the tape on a tensile testing machine at a speed of 300 mm / min. The average peeling force read on the tensile testing machine is recorded as L0. The residual rate is then calculated as L1 / L0×100%.
[0027] The test results are shown in Table 1.
[0028] Table 1 As can be seen from Table 1, the release films prepared in Examples 1-3 of the present invention significantly improve their aging and high temperature resistance due to the modification of polydimethylsiloxane with an organic compound of hydroxyethyl acrylate and cerium. After 24 hours of aging or high temperature treatment, they still maintain a low release force and a high residual adhesion rate, with essentially no residue left on the surface of the adhered object. In contrast, in Example 4, where only polydimethylsiloxane is modified by copolymerization, the release film prepared therefrom has a release force only slightly higher than that of Examples 1-3 at high temperature, but a lower residual adhesion rate. In contrast, in Comparative Example 1, where no polydimethylsiloxane is modified, the release film prepared therefrom has the highest release force and the lowest residual adhesion rate, potentially resulting in severe silicone oil residue and the worst performance. In Comparative Example 2, where a modified polydimethylsiloxane according to the prior art is used to prepare the release film, although its release force is relatively low, its release force is relatively high at high temperatures, its properties are unstable, and its residual adhesion rate is low, resulting in silicone oil residue. In summary, the release film prepared by the present invention has a low release force, is easier to peel off the material surface, has a high adhesion residue rate, and basically does not cause silicone oil residue. It can be better used in high-end electronics, new energy, automobiles and other fields.
[0029] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing a PE embossed breakpoint release film, characterized in that: The following steps are involved: Step 1: dissolving modified polydimethylsiloxane and a cross-linking agent in a solvent, adding a catalyst and a regulator, stirring evenly, and filtering to obtain a release agent; Step 2: Use a flattening roller to eliminate wrinkles on the PE film, then perform corona treatment on the PE film, apply a release agent on the PE film and heat-cure it to obtain a release film; Step 3: Use an embossing machine to emboss the release film into patterns, then mark breakpoints, and finally roll it up to obtain a PE embossed breakpoint release film.
2. The method for preparing the PE embossed breakpoint release film according to claim 1, wherein: In the step 1, the mass ratio of modified polydimethylsiloxane, cross-linking agent, solvent, catalyst and regulator is 10-15:4-6:60-70:0.3-0.5:5-10.
3. The method for preparing the PE embossed breakpoint release film according to claim 1, wherein: In the step 1, the crosslinking agent is one of hydrogen-containing silicone oil, methyl hydrogen-containing silicone oil, diethylenetriamine, and ethylenediamine; the solvent is one of toluene, xylene, dichloromethane, chloroform, tetrahydrofuran, and ethyl acetate; the catalyst is a platinum catalyst; and the regulator is one of stearic acid, butyl stearate, oleamide, ethylene bisstearamide, and polyethylene wax.
4. The method for preparing the PE embossed breakpoint release film according to claim 1, wherein: In the step 1, the stirring speed is 300-500 rpm, and the stirring is carried out at 30-40° C. for 1-2 hours.
5. The method for preparing the PE embossed breakpoint release film according to claim 1, wherein: In the step 2, corona treatment is performed in a corona device for 20 to 30 minutes at a corona voltage of 50 to 60 kV.
6. The method for preparing the PE embossed breakpoint release film according to claim 1, wherein: In the step 2, the release agent is coated with a thickness of 0.05-0.08 mm, the curing temperature is 60-80° C., and the heating time is 8-10 minutes.
7. The method for preparing the PE embossed breakpoint release film according to claim 1, wherein: In the step 1, the preparation method of modified polydimethylsiloxane is specifically as follows: S1. Dissolve polydimethylsiloxane in isooctane, then add hydroxyethyl acrylate, then add azobisisoheptanenitrile and N,N-methylenebisacrylamide, and heat to react for a period of time under an argon atmosphere; S2, adding the cerium-containing organic compound to the system after the reaction in S1, heating and reacting for a period of time under an argon atmosphere again, and then cooling to room temperature, turning off the argon, filtering the solid-liquid mixture under reduced pressure, and collecting the filtrate; S3. The filtrate is transferred to a degassing reactor, and low-boiling substances are removed under argon protection. After completion, the temperature is cooled to room temperature, and the argon is turned off to obtain modified polydimethylsiloxane.
8. The method for preparing the PE embossed breakpoint release film according to claim 7, wherein: In S1, the mass ratio of polydimethylsiloxane, isooctane, hydroxyethyl acrylate, azobisisoheptonitrile and N,N-methylenebisacrylamide is 1:8-10:0.4-0.5:0.02-0.03:0.02-0.03, and the heating reaction is performed at a temperature of 80-90° C. for 6-8 hours.
9. The method for preparing the PE embossed breakpoint release film according to claim 7, wherein: In S2, the amount of the cerium-containing organic compound added is 3-5 wt % of the initial polydimethylsiloxane, the cerium-containing organic compound is one or more of cerium acetylacetonate, cerium acetylacetonate hydrate, and cerium isooctanoate, the heating temperature is 180-200° C., and the heating time is 12-18 hours.
10. The method for preparing the PE embossed breakpoint release film according to claim 7, wherein: In the step S3, the operation temperature for removing low boiling materials is 220-250°C, the operation time is 3-6 hours, and the absolute pressure is 10 -5 ~3000Pa.
Citation Information
Patent Citations
A matte release film
CN105348946B
An organosilicon release agent with ultra-light release force and its preparation method
CN110819261B
An ultra-light fluorine release film
CN116120614B